Periodic Heat Stress Licenses EMSC Differentiation into Osteoblasts via YAP Signaling Pathway Activation - Wentao Shi; Zhe Wang; Lu Bian; Yiqing Wu; Mei HuiYa; Yanjun Zhou; Zhijian Zhang; Qing Wang; Peng Zhao; Xiaojie Lu (Stem Cells International)
Background. The repair and regeneration of large bone defects represent highly challenging tasks in bone tissue engineering. Although recent studies have shown that osteogenesis is stimulated by periodic heat stress, the thermal regulation of osteogenic differentiation in ectomesenchymal stem cells (EMSCs) is not well studied. Methods and Results. In this study, the direct effects of periodic heat stress on the differentiation of EMSCs into osteoblasts were investigated. EMSCs derived from rat nasal respiratory mucosa were seeded onto culture plates, followed by 1 h of heat stress at 41°C every 7 days during osteogenic differentiation. Based on the results of the present study, periodic heating increases alkaline phosphatase (ALP) activity, upregulates osteogenic-related proteins, and promotes EMSC mineralization. In particular, increased YAP nuclear translocation and YAP knockdown inhibited osteogenic differentiation induced by heat stress. Furthermore, the expression and activity of transglutaminase 2 (TG2) were significantly increased after YAP nuclear translocation. Conclusion. Together, these results indicate that YAP plays a key role in regulating cellular proteostasis under stressful cellular conditions by modulating the TG2 response.